Recognition of transition metals by benzimidazoles with an optical response - Esteves, Cátia Isabel Canavezes (2015)
Comunicação eletrónica d003 apresentada na 19th Int. Electron. Conf. Synth. Org. Chem., 1–30 Novembro 2015. Sciforum Electronic Conference Series, Vol. 19